Ethereal Lenscraft Company Profile UI/UX Design Using Design Thinking Approach - Azis, Zulkifli; Sugianto, Rulliansyah (Universitas Trilogi, 2025)
Ethereal Lenscraft is a company specializing in photography and videography, with its company profile designed to effectively market its services. The primary focus of the website is to enhance user interactivity and satisfaction for those seeking documentation services for their events. Therefore, it is essential to conduct research from a design perspective, particularly in terms of UI/UX. This study employs the Design Thinking methodology to enhance the user interface (UI) and user experience (UX) of the